Impact of Storage Conditions on Salmonella enterica and Listeria monocytogenes in Pre- and Post-Printed 3D Food Ink - Allyson N. Hamilton; Kristen E. Gibson (Journal of Food Protection)
3D food printers (3DFPs) allow for the customization of physicochemical properties of foods in new ways. Storage conditions for food ink capsules and printed food inks have not been investigated. This study aimed to determine the impact of storage temperature, time, and method (pre- vs. postprinting) on Salmonella enterica and Listeria monocytogenes. A bacterial cocktail was cultured in minimal media and added to a protein cookie food ink at ∼6.5 log CFU/g. The inoculated food ink was divided into 18 capsules (50 g/capsule); half were 3D printed. The remaining capsules and printed products were stored at three temperatures [20 °C, 4 °C, −18 °C]. Selective media (XLT-4 and CHROMagar Listeria) were used for pathogen enumeration. Aerobic plate count and yeast counts were performed at each time point. The pH and water activity (aw) of the food ink were measured at the initial and final timepoints. A significant four-way interaction effect was observed between microorganism type (L. monocytogenes/Salmonella), time, temperature, and storage method (capsule/print) (p = 0.014). Significant findings include (1) at −18 °C, concentrations of L. monocytogenes decreased between Day 0 and Day 1, (2) at 20 °C, concentrations of S. enterica were significantly higher in the capsule than in the printed food on Day 1 (p < 0.0001), and (3) at 4 °C, concentrations of S. enterica were significantly higher in the printed food on Day 5 compared to Day 1 (p < 0.0001) with a 0.9 (95% CI: 0.89, 0.91) log increase. In addition, a significant three-way interaction effect was found between microorganism type (yeast/aerobic counts), time, and temperature (p = 0.024). Yeast counts remained steady at all temperatures, while aerobic counts increased at 4 °C. Minimal differences were observed between Listeria and Salmonella and their responses to varying storage conditions over time indicating that storage method and temperature may be less important for a low-water activity product such as protein cookie food ink.